Networks of counterparties in the centrally cleared EU-wide interest rate derivatives market - Paweł Fiedor; Sarah Lapschies; Lucia Orszaghova (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2017)
We perform a network analysis of the centrally cleared interest rate derivatives market in the European Union, by looking at counterparty relations within both direct (house) clearing and client clearing. Since the majority of the gross notional is transferred within central counterparties and their clearing members, client clearing is often neglected in the literature, despite its significance in terms of net exposures. We find that the client clearing structure is very strongly interconnected and contains on the order of 90% of the counterparty relations in the interest rate derivatives market. Moreover, it is more diverse in terms of geography and sectors of the financial market the counterparties are associated with. Client clearing is also significantly more volatile in time than direct clearing. These findings underline the importance of analysing the structure and stability of both direct and client clearing of the interest rate derivatives market in Europe, to improve understanding of this important market and potential contagion mechanisms within it.
Keywords: G10; L14; G23; 330; systemic risk; interconnectedness; financial networks; interest rate derivatives; central counterparties; client clearing; EMIR data